How flow becomes turbulent - Chen, Jim C. (2014)
Sub-harmonic resonance in zero pressure gradient three-dimensional boundary layer flow occurs in the classical N-type pathway of turbulence transition.Three-dimensionality incurs exorbitant computational demands on the numerical simulations. Imposition of a spectral method and a non-uniform grid countervails the impractical computational demands.Eigenvalue analysis ascertains ranges of stability of the numerical method. Validation of the numerical method versus the three-dimensional OS equation avers confidence in the accuracy of the model. Numerical realizations of the generation, amplification, and interaction of two- and three-dimensional sub-harmonic waves agree qualitatively with classical experiments.